QUESTION CAREER PATH ACEH SHARIA POLICE - Armia, Muhammad Siddiq (Universitas Islam Negeri Ar-Raniry, 2023)
After more than a decade of imposing Islamic law in Aceh, appearing various legal problems such as career path of Sharia Police or known as Wilayatul Hisbah (WH). In one hand, WH is faced on commitment of working harder by upholding religious norms as well as national regulations. On the other hands, their career path does not have a future certainty, even futureless. In the Act of Government of Aceh WH positions hand in hand with Satuan Polisi Pamong Praja (Satpol PP), having specific task to uphold general bylaws. Unfortunately in national level there are no single regulations arranging a path of professional career for WH. This fact contributes on hesitation of WH members to pursue their future career. Some of them switch their position to other career paths, having more certainty in national level. From the perspective of budged use, skill training cost for WH members are very expensive. If most of them change their future career, it will be a big loss for national budget, because their skill cannot be used for WH development. Thus, it needs a breakthrough to resolve this problem